Entrepreneurship education at universities : learning from twenty European cases - Volkmann, Christine K.; Audretsch, David B. (Springer, 2017)
This volume discusses entrepreneurship education in Europe on the basis of in-depth case studies of related activities at twenty higher education institutions. Based on a model of entrepreneurship education, the analysis addresses curricular and extra-curricular teaching, as well as the institutional and stakeholder context of delivering entrepreneurship education within higher educational institutions. The book offers both insightful entrepreneurship teaching practices and a discussion of potential organizational drivers and barriers. Accordingly, it provides a valuable resource for researchers, instructors, and managers of entrepreneurship education alike.
Keywords: Entrepreneurship -- Study and teaching (Higher) -- Europe -- Case studies.; Education, Higher -- Europe -- Case studies.; Entrepreneurship -- Europe -- Case studies.; Europe.; elektronické knihy; electronic books